Throwing your hat in the ring: Women volunteers in boxing. Issue 10 (3rd October 2022) - Fitzgerald, Hayley; Stride, Annette; Drury, Scarlett
Abstract: This paper focuses on part of a research project that considers women's sports volunteering experiences. Specifically, we draw on interview data with four women boxing volunteers. Research focusing on boxing and gender has largely been preoccupied with the politics of women's inclusion in competitive boxing, media coverage, and women boxers' gendered identities. Less attention is given to women who volunteer within boxing clubs. Theoretically we use feminist-queer thinking, which challenges structural constraints whilst incorporating post-structural and queer deconstructive approaches towards understanding the gendered body. To re-present the women's accounts we offer a story, ' The boxing gym: A women's volunteering story', and discuss three themes: women as an exception in boxing; women having to prove themselves; and women's sense of belonging within their boxing community. Our closing remarks highlight the precarious position of women volunteers in boxing and reiterate their role as pivotal constituents in sustaining the future of boxing communities.